Precautionary and Liquidity Line-Operational Guidance Note. (Policy Papers; Policy Paper ;, 2012)
The Precautionary and Liquidity Line (PLL) was introduced in the context of the Board discussion on the Fund's Financing Role: Reform Proposals on Liquidity and Emergency Assistance in November 2011, replacing and broadening the scope of the previously established Precautionary Credit Line (PCL). The following note provides operational guidance to staff and further background information on the PLL. SPR (the Emerging Markets Division), FIN, and LEG stand ready to clarify any further questions that departments may have on the PLL.